Bortezomib reinduction chemotherapy in high‐risk ALL in first relapse: a report from the Children's Oncology Group - Horton, Terzah M.; Whitlock, James A.; Lu, Xiaomin; O'Brien, Maureen M.; Borowitz, Michael J.; Devidas, Meenakshi; Raetz, Elizabeth A.; Brown, Patrick A.; Carroll, William L.; Hunger, Stephen P. (British journal of haematology, 2019)
Summary While survival in paediatric acute lymphoblastic leukaemia (ALL) is excellent, survival following relapse is poor. Previous studies suggest proteasome inhibition with chemotherapy improves relapse ALL response rates. This phase 2 Children's Oncology Group study tested the hypothesis that adding the proteasome inhibitor bortezomib to chemotherapy increases complete response rates (CR2). Evaluable patients (n = 135, 103 B‐ALL, 22 T‐ALL, 10 T‐lymphoblastic lymphoma) were treated with reinduction chemotherapy plus bortezomib. Overall CR2 rates were 68 ± 5% for precursor B‐ALL patients (<21 years of age), 63 ± 7% for very early relapse (<18 months from diagnosis) and 72 ± 6% for early relapse (18–36 months from diagnosis). Relapsed T‐ALL patients had an encouraging CR2 rate of 68 ± 10%. End of induction minimal residual disease (MRD) significantly predicted survival. MRD negative (MRDneg; MRD <0·01%) rates increased from 29% (post‐cycle 1) to 64% following cycle 3. Very early relapse, end‐of‐induction MRDneg precursor B‐ALL patients had 70 ± 14% 3‐year event‐free (EFS) and overall survival (OS) rates, vs. 3‐year EFS/OS of 0–3% (P = 0·0001) for MRDpos (MRD ≥0·01) patients. Early relapse patients had similar outcomes (MRDneg 3‐year EFS/OS 58–65% vs. MRDpos 10–19%, EFS P = 0·0014). These data suggest that adding bortezomib to chemotherapy in certain ALL subgroups, such as T‐cell ALL, is worthy of further investigation. This study is registered at http://www.clinical.trials.gov as NCT00873093.